Examining Relational Concepts in Manggarai's Penti Culture through Martin Buber's Philosophy of Relational Dialogue - Adon, Mathias Jebaru (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2023)
This study examines the concept of relationality within the Penti culture embraced by the Manggarai people, with special reference to Martin Buber's philosophy of relational dialogue. The primary focus of this study centers on the rituals woven into the fabric of the Penti celebration. The Penti celebration signifies the Manggarai people's profound appreciation for their fellow humans, nature, and the Creator. Within Manggarai belief systems, the preservation of Penti culture is regarded as an obligation, given its repository of invaluable life wisdom values such as brotherhood, cooperation, and reconciliation. Conducted as a literature study, this research employs Martin Buber's philosophy of relational dialogue as an analytical framework to illuminate the concept of relationality embedded in Penti celebration. The findings of this study underscore that Penti serves not only as a harvest thanksgiving celebration but also as a way of life, fostering connections with fellow humans, nature, and the Creator. The Penti celebration also unveils the identity of the Manggarai people as a community that upholds the principles of solidarity among fellow humans, reverence for nature, and respect for the Creator. In general, this research on the Penti celebration enriches the growing studies of local wisdom in Indonesia.